2020
DOI: 10.3343/alm.2020.40.6.466
|View full text |Cite
|
Sign up to set email alerts
|

Proenkephalin Predicts Organ Failure, Renal Replacement Therapy, and Mortality in Patients With Sepsis

Abstract: Background Kidney failure occurs frequently and is associated with high mortality during sepsis. Proenkephalin (PENK) is an emerging biomarker of kidney function. We explored whether PENK levels could predict severity, organ failure, and mortality in septic patients. Methods We measured the PENK level in the plasma of 215 septic patients using the sphingotest penKid assay (Sphingotec GmbH, Hennigsdorf, Germany). This was analyzed in terms of sepsis severity, vasopressor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…The 28- or 30-day mortality from sepsis diagnosed using the Sepsis-3 criteria was 22.7% (95% confidence interval [CI], 20.0%–25.6%; I 2 =89%) ( Table 2 and Fig. 2 ) [ 15 , 17 , 21 , 26 , 27 , 35 , 39 , 42 , 46 , 50 , 55 – 59 , 69 , 72 ]. The range of mortality in the included studies was 14.4% to 40.8%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 28- or 30-day mortality from sepsis diagnosed using the Sepsis-3 criteria was 22.7% (95% confidence interval [CI], 20.0%–25.6%; I 2 =89%) ( Table 2 and Fig. 2 ) [ 15 , 17 , 21 , 26 , 27 , 35 , 39 , 42 , 46 , 50 , 55 – 59 , 69 , 72 ]. The range of mortality in the included studies was 14.4% to 40.8%.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the 28- or 30-day mortality rate by including all sepsis criteria was 24.8% (95% CI, 22.1%–27.7%; I 2 =95%) ( Supplementary Fig. 1 ) [ 15 , 17 , 20 , 21 , 26 , 27 , 29 – 31 , 34 , 35 , 39 , 42 , 44 , 46 , 50 , 55 – 59 , 63 , 69 , 71 , 72 , 74 ]. In the subgroup analyses, 28- or 30-day mortality from sepsis was 22.6% (95% CI, 19.5%–25.9%; I 2 =94%) in retrospective cohort studies, 29.1% (95% CI, 23.4%–35.5%; I 2 =96%) in prospective studies, 23.3% (95% CI, 20.5%–26.5%; I 2 =93%) in single-center studies, and 31.3% (95% CI, 23.4%–40.4%; I 2 =98%) in multicenter studies ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…This result implies that HBP concentration may be high without sepsis or other known ill conditions. Several biomarkers, including biologically active adrenomedullin and proenkephalin, have been reported that could be objective and useful markers to predict severity, organ failure, and mortality in septic patients [ 29 , 30 ]. Since the concentration of these biomarkers vary among individuals, it is mandatory to understand the biological variation (BV) of a biomarker in healthy individuals [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The higher the level of these indicators, the more serious the sepsis. Multiple organ failure and persistent organ failure are among the most important risk factors for poor prognosis (17)(18)(19), and 28-day mortality is the most important prognosis index. Combined with the results of this study, BPV has a substantial value in predicting the prognosis of patients with sepsis, which is closely related to the severity of sepsis, and it is worthy of further study.…”
Section: Discussionmentioning
confidence: 99%